SOSIALISASI PENINGKATAN KESADARAN SANITASI DAN KESEHATAN LINGKUNGAN BAGI PELAJAR SEKOLAH DASAR DI TERNATE - Ayu, Yusmar Yusuf; Bahtiar, Bahtiar; Tala, W.D. Syarni; Haerullah, Ade; Suparman, Suparman; Rasyid, Magfirah; Saibi, Ningsi; Salewangen, Aswal; Sabar, Mesrawaty; Hidayat, Hapsah Usman (Universitas Mataram, 2024)
Improving school sanitation is the first step in creating a conducive learning environment, which can trigger improvements in the quality of students' health. Various efforts have been made by SD Alkhairaat 02 Kota Ternate to create a healthy school environment, namely by preparing sanitation installations such as toilets and clean water, hand washing facilities and rubbish disposal areas. SD Alkhairaat 02 Kota Ternate is also trying to increase awareness about the importance of sanitation and environmental health among students by collaborating with external parties. This activity aims to increase students' awareness of environmental sanitation and health, as well as support the development of the school's environmental sanitation and health profile. This socialization activity was carried out at SD Alkhaeraat 02 Kota Ternate. This socialization activity consists of 4 stages, namely the preparation stage, socialization (exposure to material), practical implementation of sanitation and environmental health, and the activity evaluation stage. The implementation of the activity stages took place smoothly and orderly, and all participants were very enthusiastic about taking part in this activity. This socialization was able to increase awareness of sanitation and personal health, this can be seen from the evaluation results of the level of areness after the activity was carried out which was categorized as very good. Socialization to increase awareness of sanitation and environmental health for elementary school students needs to be carried out continuously and consistently, well planned, involving relevant stakeholders.